Identification and validation of Sertoli cell homing peptides as molecular steering for testis targeted drug delivery. (21st April 2023) - Jirwankar, Yugandhara; Dighe, Vikas
Abstract: The testicle, an organ privileged with immunity because of Blood-Testis Barrier (BTB), poses a major impediment to developing and delivering drugs to the testes. These problems can be prevented by targeting testicular cells using specific ligands, such as homing peptides. This is the first study to demonstrate the successful selection of Sertoli cell homing peptides using a phage display peptide library. The identification of peptides is performed with Sanger sequencing and high-throughput NGS. The Sertoli cell and testis targeting potential of the SCHP1 and SCHP2 was confirmed using confocal microscopy and flow cytometry of the FITC-labelled peptides and in vivo bio-distribution of the corresponding Cy5.5-tagged peptides. Secondary structures were predicted in the setting of different polarity by circular dichroism. The results suggest that SCHP1 and SCHP2 can effectively target Sertoli cells. In vivo bio-distribution in mouse models indicated significantly higher uptake of SCHP1 and SCHP2 by testes compared with the heart, brain, and spleen. SCHP1 and SCHP2 can be adopted as molecular steering for targeted male contraceptive delivery, treatment of testicular cancer, and male infertility. Further development of the peptides into peptidomimetics may increase their stability, and information on the molecular targets of these peptides may reveal their therapeutic potential.